Spinal Intramedullary Ependymal Cysts : A Case Report and Review of the Literature - Park, Chang Hyun (The Korean Neurosurgical Society, 2012)
We report a rare case of a spinal intramedullary ependymal cyst in a 46-year-old female and review the 17 pathologically proven cases in the literature. The patient presented with a two-week history of gradually increasing tingling in her left posterior thigh and calf. A preoperative magnetic resonance image revealed a well-defined intramedullary cystic lesion on the ventral side of the spinal cord at the T11 to T12 levels. The lesion was hyper intense in T2-weighted images and hypointense in T1-weighted. The patient underwent a right-side hemilaminectomy at the T11 to T12 levels and fenestration of the cyst wall. After having the cyst wall partially removed and communication established between the cyst and the subarachnoid space, the patient improved neurologically. A histological study of the surgical specimens revealed that the cyst wall consisted of glial cells lined by a simple cuboidal to columnar epithelium. An immunohistochemical examination of the cells lining the cyst wall was positive for S-100 protein, glial fibrillary acidic protein, epithelial membrane antigen, and cytokeratin. We suggest that the optimal treatment of intramedullary ependymal cysts creates adequate communication between the cyst and the subarachnoid space.